2016
DOI: 10.1002/osp4.43
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between serum irisin levels and metabolic parameters in Japanese patients with obesity

Abstract: SummaryBackground/PurposeIrisin is a skeletal muscle myokine that causes the brown coloration of white fat, promotes fat burning, inhibits weight gain and may be useful for treatment of obesity. Irisin is also related to glucose/lipid metabolism and may prevent onset of diabetes, but a consensus on irisin secretion has not been reached. The purpose of this study was to determine the relationships between serum irisin levels and physical factors in untreated Japanese men and women with obesity.MethodsThe subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 32 publications
7
32
2
Order By: Relevance
“…Conversely, in our Caucasian cohort in the early stages of aging, the association between irisin, insulin levels and HOMA index was significant in both genders, in agreement with previous reports in younger Asian populations [21] and with the meta-analysis by Qiu et al [10]. In our series, sex differences were maintained across IR severity stages.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Conversely, in our Caucasian cohort in the early stages of aging, the association between irisin, insulin levels and HOMA index was significant in both genders, in agreement with previous reports in younger Asian populations [21] and with the meta-analysis by Qiu et al [10]. In our series, sex differences were maintained across IR severity stages.…”
Section: Discussionsupporting
confidence: 93%
“…Gender-differences in irisin levels have been observed: women consistently displaying higher values than men among Saudi children [19], middle-aged Chinese [20] and Japanese adults [21]. The divergent results from studies performed in healthy, non OB, and young population [22,23] may be ascribed to the physiologically higher muscle mass in males compared to females, in the absence of increased excess body fat.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, Al-Daghri et al observed negative association between irisin and fasting glucose and HOMA-IR in school-age Saudi boys and girls [ 63 ]. Conversely, there are positive associations between irisin and insulin concentration, fasting glucose, and HOMA-IR [ 64 , 65 , 66 , 67 ]. Fukushima et al analyzed a positive correlation on obese men and adult women [ 66 ], while Pardo et al determined a correlation in women with anorexia nervosa, normal weight, and obesity [ 65 ].…”
Section: Irisin Structure and Functionmentioning
confidence: 99%
“…Animal studies also demonstrated the effects of female sex hormones in irisin levels among ovariectomized female rats, but not in orchidectomized male rats [23]. Furthermore, the association of irisin levels in glycemic metabolism is reinforced in several recent studies, with elevated irisin levels being an independent predictor of diabetes mellitus and Homeostatic Model Assessment -Insulin Resistance (HOMA-IR) in adults [24,25]. The association of irisin however to insulin resistance is positive in adults as opposed to inverse association in children in our 2014 study.…”
Section: No Reperfusion 1-min Reperfusion 1-week Reperfusion 1-month mentioning
confidence: 99%